2014
DOI: 10.1038/psp.2013.74
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Model of Drug‐Induced Liver Injury Aids the Interpretation of Elevated Liver Transaminase Levels in a Phase I Clinical Trial

Abstract: Entolimod (CBLB502) is a Toll-like receptor 5 agonist in development as a single-dose countermeasure against total body irradiation. Efficacy can be assessed from animal studies, but the “Animal Rule” does not apply to safety assessment. Marked elevations of serum aminotransferases (exceeding 1,000 IU/l) were observed in some human subjects receiving Entolimod in a safety study, threatening its continued development. The percentage of total hepatocytes undergoing necrosis in these subjects was estimated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 24 publications
(64 reference statements)
1
26
0
1
Order By: Relevance
“…It is well known that many toxic compounds accumulate in the liver where they are detoxified [30]. Liver transaminases such as AST (aspartate transaminase) or SGOT (serum glutamic oxaloacetic transaminase), and ALT (alanine transaminase) or SGPT (serum glutamic pyruvic transaminase) have still remained the gold standards for the assessment of liver injury [31]. So in the present investigation, there were significant (p>0.0001) increased levels of SGOT, SGPT and total bilirubin along with increased LDH enzyme activity in paracetamol hepatic damage group in comparison to control group.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that many toxic compounds accumulate in the liver where they are detoxified [30]. Liver transaminases such as AST (aspartate transaminase) or SGOT (serum glutamic oxaloacetic transaminase), and ALT (alanine transaminase) or SGPT (serum glutamic pyruvic transaminase) have still remained the gold standards for the assessment of liver injury [31]. So in the present investigation, there were significant (p>0.0001) increased levels of SGOT, SGPT and total bilirubin along with increased LDH enzyme activity in paracetamol hepatic damage group in comparison to control group.…”
Section: Discussionmentioning
confidence: 99%
“…However, the peak serum ALT values occurred very quickly after dosing and the levels then fell very rapidly, indicating a very short duration of hepatocyte death. Based on serial ALT measurements collected from these responders, DILIsym software was able to estimate that at most a loss of 4.9% of hepatocytes occurred in the most affected participant receiving Entolimod . To put this into context, liver biopsy data collected from patients suffering from an acetaminophen overdose has demonstrated that about 30% of liver volume must be lost before liver function decline is sufficient to result in TBIL >2× ULN …”
Section: Making the Most Of Traditional Biomarkers: In Silico Modelingmentioning
confidence: 99%
“…In the case of Entolimod, ALT peaked quickly and returned to baseline quickly. In a different scenario an ALT peak of a similar magnitude but gradual reduction would be predicted to cause a much greater loss of hepatocytes . Recently, a mathematical equation incorporating ALT peak the area under the receiver operating characteristic curve values has been proposed to approximate values obtained with DILIsym, especially with DILI events of short duration …”
Section: Making the Most Of Traditional Biomarkers: In Silico Modelingmentioning
confidence: 99%
“…Enzyme such as AST and ALT are main liver transaminases have been used for the assessment of liver damage (Howell et al, 2014).…”
Section: Biological Activitymentioning
confidence: 99%